Elastomeric Pillar Cages Modulate Actomyosin Contractility of Epithelial Microtissues by Substrate Stiffness and Topography - Lisann Esser; Ronald Springer; Georg Dreissen; Lukas Lövenich; Jens Konrad; Nico Hampe; Rudolf Merkel; Bernd Hoffmann; Erik Noetzel (Cells, 2023)
Cell contractility regulates epithelial tissue geometry development and homeostasis. The underlying mechanobiological regulation circuits are poorly understood and experimentally challenging. We developed an elastomeric pillar cage (EPC) array to quantify cell contractility as a mechanoresponse of epithelial microtissues to substrate stiffness and topography. The spatially confined EPC geometry consisted of 24 circularly arranged slender pillars (1.2 MPa, height: 50 µm; diameter: 10 µm, distance: 5 µm). These high-aspect-ratio pillars were confined at both ends by planar substrates with different stiffness (0.15–1.2 MPa). Analytical modeling and finite elements simulation retrieved cell forces from pillar displacements. For evaluation, highly contractile myofibroblasts and cardiomyocytes were assessed to demonstrate that the EPC device can resolve static and dynamic cellular force modes. Human breast (MCF10A) and skin (HaCaT) cells grew as adherence junction-stabilized 3D microtissues within the EPC geometry. Planar substrate areas triggered the spread of monolayered clusters with substrate stiffness-dependent actin stress fiber (SF)-formation and substantial single-cell actomyosin contractility (150–200 nN). Within the same continuous microtissues, the pillar-ring topography induced the growth of bilayered cell tubes. The low effective pillar stiffness overwrote cellular sensing of the high substrate stiffness and induced SF-lacking roundish cell shapes with extremely low cortical actin tension (11–15 nN). This work introduced a versatile biophysical tool to explore mechanobiological regulation circuits driving low- and high-tensional states during microtissue development and homeostasis. EPC arrays facilitate simultaneously analyzing the impact of planar substrate stiffness and topography on microtissue contractility, hence microtissue geometry and function.